Peran Instrumen Keuangan Syariah Dalam Mendorong Stabilitas Ekonomi Nasional: instrumen keuangan syariah - Gusnawati Nurbaba; Syahriyah Semaun (At-Tanmiyah Jurnal Ekonomi dan Bisnis Islam, 2025)
Islamic financial instruments play a vital role in maintaining national economic stability through principles of justice, partnership, and linkage to the real sector. This study employs a descriptive qualitative method using literature review to analyze the contribution of four key instruments: Islamic banking, Islamic capital markets and sukuk, productive zakat and waqf, and Islamic microfinance institutions. The results show that these instruments complement one another in strengthening the real sector, expanding financial inclusion, and reducing economic inequality. Their synergy creates a more resilient, equitable, and sustainable financial system, making it a key pillar of Indonesia’s economic stability. Keywords: Islamic finance, economic stability, sukuk, productive waqf, Islamic microfinance institutions.